Tantangan Industri di Indonesia dan Strategi Penjualan melalui Diferensiasi dan Advertensi - Muchammad Aditya Ferdiansyah; Muhammad Yasin (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This research aims to analyze the industrial challenges faced by small and medium enterprises (SMEs) in Indonesia and explore sales strategies through differentiation and advertising to improve business performance. Using quantitative methods, this research involved 100 respondents consisting of SME entrepreneurs in various industrial sectors in Indonesia. Data was collected through questionnaires and analyzed using regression analysis techniques to test the influence of these variables on sales performance. The research results show that industrial challenges such as limited access to technology and capital have a negative effect on SME performance, while product differentiation and digital advertising strategies are proven to increase the competitiveness and sales performance of SMEs. This research also contributes to the understanding of the importance of innovation in products and effective marketing to face competitive market challenges. The practical implication of this research is the need to increase investment in product innovation and digital marketing to strengthen the position of SMEs in the market. This research also provides recommendations to the government to provide support in the form of policies that facilitate access to technology and capital for SMEs.